FUNGSI MINIATUR CANDI ZAMAN KLASIK MUDA MASA KERAJAAN SINGASARI - Fadlikal . M, Achmad; ALRIANINGRUM, SEPTINA (Avatara, 2020)
The temple is a religious sacred building that was built in the classical period in Indonesia, which is 8-15 AD century. The division of the temple period in Java is divided into two periods, the Old Classic (Ages 8-10 M), scattered in Central Java and the Young Classic period (Ages 11-15 M) spread across East Java. The architecture of the temple has a change in development from the Old Classic period to the Young Classic Period, one of which is the miniature component of the temple which is at the junction of the temples stairs with the foot wall of the temple. Miniature temples are located at the junction between the walls of the temple steps with the foot wall, but not all temples have a temple miniature at the meeting between the temple steps and the temple foot walls. The miniature architectural component of the temple was found in the Old Classical period found in the Shiva Prambanan Temple and found again in the heritage temple of the Kingdom of Singasari. Each architectural component has a purpose and purpose, the miniature component of the temple has diversity in terms of the shape and layout of the miniature, so researchers are interested in examining the temple miniature. Miniature temples that have diversity in terms of shape and location are interesting phenomena to discuss. This research focuses on two problems, namely, (1) What is the shape and location of miniature temples from the Singosari Kingdom; (2) How is the function of miniature temples from the Singasari Kingdom. Diversity in terms of the shape and location of the miniatures and their functions can be known by making comparisons with miniature temples in the previous period both the relics of the temple in the Old Classical period. Researchers use historical research methods consisting of stages (1) Heuristics through literature studies and observations in the field, (2) Criticism, (3) Interpretation, and (4) Historiography. The results showed the miniature of the temple inheritance of the Kingdom of Singasari, there is a diversity of forms and layout of the miniature which has a two-sided and three-sided basic shape and its location is not always right at the temples stairs with the temple foot wall but rather shifts to the temples staircase walls. The heritage of Singasari Kingdom which has a miniature component of the temple inside is found in Kidal Temple, Jago Temple and Jawi Temple. Miniature temples become an architectural component that has a function as a liaison architectural building temples from the Classical Period and a component that protects the midpoint of the temple (Brahmasthana) in the architectural system of the temple. Keywords: Temple Functoin, Temple Miniature, Singasari Kingdom